ChemInform Abstract: Catalytic α‐Alkylation/Reduction of Ketones with Primary Alcohols to Furnish Secondary Alcohols. Issue 17 (April 2016) - Lundberg, Helena; Adolfsson, Hans
Abstract: Review: [38 refs.